Kings of disaster: dualism, centralism and the scapegoat king in Southeastern Sudan - Simonse, Simon (Studies in Human Society Series, 1992)
A comparative study of the political organization of five Eastern Nilotic peoples based on field work and written sources, analyzed in the light of Rene Girard's victimary anthropology. Regicide (several recent case studies) appears as a logical and necessary practice in these political systems which are neither segmentary nor states.